GELMA BASED 3D BIOPRINTING IN REGENERATIVE MEDICINE - Hazra, Subhajit; Predheepan, Dhakshanya; S, Jeba Samuel C; V, GovindanT.; Singh, Ripudaman (Journal of Biomedical and Pharmaceutical Research, 2021)
Over the past few years, research and progress in 3D printing have become evident. The process of bioprinting involves the use of a bioink composed of human cells or tissue. For example, 3D printing in organ transplantation aims to develop an organ that can synchronize with other physiologic components. In the past ten years, bioprinting has made a substantial leap. It has been used in the fabrication of living tissues for its application in various areas. Moreover, this technology has also been commercialized, resulting in its significant interest from the research fraternity. Thus, this review provides a brief on the development of the field from its foundation to the current commercialization with respect to the polymer Gelatin Methacrylate. Keywords: 3D Bioprinting, Stem cells, GelMA, Regenerative Medicine